Relationship of Parity, Knowledge and Anemia Status with Perineal Wound Healing in Postpartum Mothers at PMB Bukit Sangkal Palembang Working Area in 2021 - Rosi Ratna Sari; Satra Yunola; Helni Anggraini (Science Midwifery, 2022)
Background: The impact of improper perineal wound care can cause infection and hinder the perineal wound healing process. The appearance of infection in the perineum can spread to the urinary tract or in the birth canal which can cause complications of bladder infection or infection of the birth canal. Based on the results of a preliminary study conducted by researchers at the PMB working area of ​​the Bukit Sangkal Public Health Center, Palembang City, the number of cases of childbirth in 2020 was obtained as many as 345 cases, 215 cases of deliveries with perineal sutures and 48 cases of wet perineal sutures during post-pastum follow-up visits today. eighth. The purpose of this study was to determine the relationship between parity, knowledge and anemia status with perineal wound healing in postpartum women at PMB Bukit Sangkal Palembang Working Area in 2021. This study used a quantitative method with a "Cross Sectional" approach. This research will be carried out from 09 to 31 August 2021. The population is all postpartum mothers in PMB Bukit Sangkal Palembang working area who were born at the time the research was conducted. Sampling was done randomly with the technique of "Accidental Sampling" obtained 96 people. Data processing is taken with primary and secondary data. Data were analyzed by univariate and bivariate, obtained parity at risk of 43 people (44.8%) and not at risk of 53 people (55.2%). good knowledge as many as 64 people (66.7%) and less knowledge as many as 32 people (33.3%). anemia as many as 38 people (39. 6%) and not anemia as many as 58 people (60.4%). Normal perineal wound healing was 58 people (60.4%) and old perineal wound healing was 38 people (39.6%). There is a parity relationship with perineal wound healing with a P value of 0.000 and an odds ratio of 0.385. The most normal perineal wound healing is 42 people, there is a relationship between knowledge and perineal wound healing with a P Value of 0.140 and an ods ratio of 4,529. There is a relationship between anemia and perineal wound healing. P Value 0.000 and odds ratio 0.073. So it is recommended to improve the quality of services, especially services, especially services for postpartum mothers with perineal wounds, by providing education about wound care and nutrition.